Self-compassionate motivation and athlete well-being: the critical role of distress tolerance - Walton, C. C.; Lewis, K. J.; Kirby, J.; Purcell, R.; Rice, S. M.; Osborne, M. S. (Journal of Clinical Sport Psychology, 2024)
This cross-sectional study explored athlete responses to the Compassion Motivation and Action Scales Self-Compassion Scale, examining its relationship with well-being. Athlete (N = 207; mean age 27.9 years) scores were consistent with previous population means. Scores on the Compassion Motivation and Action Scales Self-Compassion Scale did not differ between elite and nonelite athletes, nor did they correlate significantly with trait competitiveness. Significant differences emerged based on athlete well-being state, with athletes categorized as "flourishing" scoring higher on the total score and all subscales of the Compassion Motivation and Action Scales Self-Compassion Scale, as compared with those with "moderate mental health" (Cohen`s ds from 0.58 to 0.92). Furthermore, the distress tolerance subscale significantly mediated the relationship between self-compassion intentions and well-being (indirect path: B = 0.034, p < .001). The results suggest that self-compassionate intentions are not enough, and athletes may need support to tolerate the distress that comes with moving toward one`s own suffering.